Strategies for intraoperative management of the trigeminal nerve and long-term follow-up outcomes in patients with trigeminal neuralgia secondary to an intracranial epidermoid cyst - Zhang, Zhenyu; Wang, Wenhua; Yu, Feng; Kwok, Sze Chai; Wang, Yuhai; Yin, Jia (Frontiers in Surgery, 2022)
Background Epidermoid cysts (ECs) are one of the most common causes of secondary trigeminal neuralgia (TGN). However, most previous studies have primarily focused on whether complete tumor resection was achieved, and few studies have discussed the primary goal of pain relief. Objective The present study provides intraoperative strategies for trigeminal nerve (TN) management in patients with TGN secondary to an EC and observed long-term follow-up outcomes. Methods A total of 69 patients with TGN secondary to an EC at our hospitals were included (January 2011–June 2021). The same surgical team performed all surgeries using a retrosigmoid approach. After EC removal, different methods for TN management were used, including microvascular decompression (MVD), sharp capsulectomy, nerve combing and embedded cholesterol crystal excision. The epidemiological, clinical, and surgical data were extracted. Results The total EC removal rate was 92.8% (64/69). All patients achieved initial pain relief postoperatively, and 12 patients (17.4%) experienced varying degrees of hemifacial hypesthesia, which was relieved within 3–6 months. Three patients (4.3%) reported partial pain recurrence within a median follow-up period of 5.5 (0.5–10.5) years, which was relieved completely after low-dose carbamazepine administration. Conclusion The primary goal of surgical tumor removal for patients with TGN secondary to an EC is relief of the main symptom of tormenting pain. The selection of an appropriate strategy for TN, including MVD, sharp capsulectomy, nerve combing or embedded cholesterol crystal excision, should depend on the patient's situation.